Effect of microbial plant biostimulants on fruit and vegetable quality: current research lines and future perspectives - Melini, Francesca; Melini, Valentina; Luziatelli, Francesca; Abou Jaoudé, Renée; Ficca, Anna Grazia; Ruzzi, Maurizio (Frontiers in Plant Science, 2023)
Fruit and vegetables hold a prominent place in dietary guidance worldwide and, following the increasing awareness of the importance of their consumption for health, their demand has been on the rise. Fruit and vegetable production needs to be reconsidered so that it can be productive and, meantime, sustainable, resilient, and able tocan deliver healthy and nutritious diets. Microbial plant biostimulants (PBs) are a possible approach to pursuing global food security and agricultural sustainability, and their application emerged as a promising alternative or substitute to the use of agrochemicals (e.g., more efficient use of mineral and organic fertilizers or less demand and more efficient use of pesticides in integrated production systems) and as a new frontier of investigation. To the best of our knowledge, no comprehensive reviews are currently available on the effects that microbial plant biostimulants' application can have specifically on each horticultural crop. This study thus aimed to provide a state-of-the-art overview of the effects that PBs can have on the morphoanatomical, biochemical, physiological, and functional traits of the most studied crops. It emerged that most experiments occurred under greenhouse conditions; only a few field trials were carried out. Tomato, lettuce, and basil crops have been primarily treated with Arbuscular Mycorrhizal Fungi (AMF), while plant grow-promoting rhizobacteria (PGPR) metabolites were used for crops, such as strawberries and cucumbers. The literature review also pointed out that crop response to PBs is never univocal. Complex mechanisms related to the PB type, the strain, and the crop botanical family, occur.